Effect of Different Heating Process on the Photoluminescence Properties of Perovskite Eu-Doped BaZrO3 Powder - Kun-Neng Chen (Applied Sciences, 2016)
In this study, BaZrO3:Eu0.025 powder was synthesized through the solid-state reaction method with two different heating processes. For the one-step process, the BaZrO3:Eu0.025 powder was heated to 1000 °C–1400 °C for 2 h. For the two-step heating process, the BaZrO3:Eu0.025 powder was pre-heated at 800 °C for 2 h, after being cooled to room temperature and ground, then the powder was heated to 1000 °C–1400 °C again for 2 h. The optimum excitation optical wavelength of BaZrO3:Eu0.025 powders were 271 nm and the maximum intensity of the emission spectrum of BaZrO3:Eu0.025 powders increased with increasing heating temperature. The all-heated BaZrO3:Eu0.025 powders showed two strong orange emission bands peaking at the wavelengths of 574 and 596 nm and two weak emission bands peaking at 620 and 650 nm. As the heating temperatures were 1300 °C and 1400 °C, the maximum intensity of one-step heating BaZrO3:Eu0.025 powders appeared at the 5D0–7F0 (574 nm) and the maximum intensity of one-step heating BaZrO3:Eu0.025 powders appeared at the 5D0–7F1 (596 nm) transitions of Eu3+ ions, respectively.